How Meaningful are Plot‐Scale Observations and Simulations of Preferential Flow for Catchment Models? - Glaser, B. (2020)
. The Monte Carlo simulations showed that the different depth profiles of Br− tracer observed in irrigation experiments could be reproduced when vertical preferential flow was simulated with a dual‐permeability approach. However, it was not possible to identify unique parameter values for preferential flow. The direct transfer of a range of different dual‐permeability parameter sets to the catchment model revealed that the variability of simulated hydrometric catchment responses (discharge and soil moisture over 18 mo) was independent of the variability among the three irrigation experiments. More importantly, the dual‐permeability approach did not improve the match between simulated and observed discharge and soil moisture responses compared with the single‐domain reference model, where multiple soil layers with differing hydraulic conductivities had already been implemented. This suggests that including structures that allow nonuniform lateral flow was more important for reproducing the hydrological response in the Weierbach catchment than the vertical preferential flow observed at plot scale.